2016
DOI: 10.1097/sla.0000000000001099
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Emergency Appendectomy and 30-Day Postoperative Outcomes in District General Hospitals and Specialist Pediatric Surgical Centers in England, April 2001 to March 2012

Abstract: Major reductions in the number of pediatric emergency appendectomies in England over the past decade were associated with an overall increase in adverse surgical outcomes. Children operated in DGHs have more reinterventions, complications, and negative appendectomy rates than those operated in SPCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
1
13
1
Order By: Relevance
“…Our institution's overall negative appendicectomy rate of 32% (29% removing the equivocal cases) which is higher than other comparable institutions. 1 Our false negative (FN) rate was 27.5% which again is higher overall than reported in the literature. While there are obvious negative outcomes associated with delayed diagnosis of appendicitis, the option remains in these equivocal cases to repeat ultrasound if the patient deteriorates or to proceed to CT.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Our institution's overall negative appendicectomy rate of 32% (29% removing the equivocal cases) which is higher than other comparable institutions. 1 Our false negative (FN) rate was 27.5% which again is higher overall than reported in the literature. While there are obvious negative outcomes associated with delayed diagnosis of appendicitis, the option remains in these equivocal cases to repeat ultrasound if the patient deteriorates or to proceed to CT.…”
Section: Discussioncontrasting
confidence: 53%
“…Indeed, there is a >10% compilation rate reported in the recent literature. 1 However, the overall FP appendicectomy rate was 32% (n = 983) and within the clinically equivocal group that underwent ultrasound that rose to 46% showing the potential for ultrasound to reduce the rate of negative appendicectomies. Our institution's overall negative appendicectomy rate of 32% (29% removing the equivocal cases) which is higher than other comparable institutions.…”
Section: Discussionmentioning
confidence: 97%
“…The main findings of reduced complications rates at specialized pediatric surgical centers are coherent with previous studies from several different health care settings. From the UK, Giuliani et al [5] identified 11% more complications and 11% more readmissions after pediatric appendectomies in district general hospitals compared to specialized pediatric surgical centers in a large cohort of 83,679 children, whilst Collins et al [4], in a smaller cohort, identified more than 50% increased risks for reoperations and readmissions in district general hospitals compared to specialized pediatric surgical centers. Comparing pediatric surgical services to general surgical services in a local US cohort, Alexander et al [3] found reduced risks for postoperative complications (8% vs 33%) and readmissions (25% vs 66%) in perforated appendicitis, but comparable outcomes in simple appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of hospital's and surgeons' characteristics on the outcome after appendectomy in children has been investigated in previous studies, with diverging results. Management in specialized pediatric surgical centers has both been associated with reduced surgical complication rates [3][4][5][6] and comparable outcomes [7][8][9][10], compared to management in general hospitals and central general hospitals. The impact of hospital caseload of pediatric appendectomies on postoperative complication rates remains virtually unknown [11,12].…”
mentioning
confidence: 99%
“…Even among high-volume surgical pathologies such as appendicitis in children, remarkable differences in care occur on local, regional, national and international scales. [1][2][3][4][5] These differences are driven by numerous factors that include clinician preferences, resource availabilities, financial constraints, expectations of patient populations, and evidence-base insufficiencies. 2,4 Integrated pathways that standardize care are effective in reducing variation and enhancing efficiency.…”
Section: Introductionmentioning
confidence: 99%